Turbomolecular pumps on conical active magnetic bearings - Angelo BONFITTO (The Japan Society of Mechanical Engineers, 2017)
The adoption of magnetic levitation is experiencing a steady growth in the vacuum industry and, in particular, in turbomolecular pumps. Nowadays, the most common solutions for pumps of small and medium pumping capacity are based on hybrid architectures where passive magnetic bearings are combined to ceramic ball bearings. By converse, fully active magnetic suspensions with cylindrical configuration represent the standard for medium to high pumping rate machines. Although simple, the cylindrical configuration is prone to drawbacks related in particular to the strains growing in the disc of the axial actuator that motivate the investigation of alternative architectures. As shown in previous literature, the use of conical configuration, besides compacting driving electronics, seems to be promising considering that the control of the radial and axial degree of freedom is performed simultaneously by the same devices acting in two actuation planes.This paper describes the development and the experimental characterization of a turbomolecular pump supported by conical active magnetic bearings. The control design is based on a SISO decentralized technique with position and control embedded loops. A rotor centering technique based on the characterization of the current loops is exposed. The external position loop is tuned by measuring relevant transfer functions to refine the controller and allow a safe critical speed crossing. The power actuation of the eight electromagnets is performed with a three-phase configuration drive technique instead of standard H-bridges to minimize the number of power switches. Experimental results along with numerical computations obtained with simulation models are reported as proof of the validity of the modeling approach and of the conical architecture effectiveness.